COVID-19 and the Sikh Community in the UK: A Qualitative Study - Kaur, Gobinderjit (Journal of religion and health, 2022)
The COVID-19 pandemic has had, and continues to have, a significant effect on individuals worldwide, and it is clear that minority communities including the Sikh community have been particularly affected by the virus. The current study assessed the impact of the pandemic in a sample of 44 British Sikhs across 11 virtual focus groups. Three main themes emerged including making meaningful connections, struggling to adjust and the organisation of gurdware (Sikh places of worship) in coping with the COVID-19 pandemic. Findings highlight that faith may promote collective action for collective healing especially during mass trauma, with specific insight into what this may entail for the Sikh community.